Investigating aggregation bias in the case of the interest rate pass-through - Jane Bogoev; Bruno S. Sergi (Intereconomics, 2012)
This analysis examines aggregation bias in the case of the interest rate pass-through in the Republic of Macedonia. By using bank-level data, the authors investigate whether there are heterogeneities and asymmetries in the size and speed of the adjustment of lending rates to changes in the cost of the funds rate. The findings in general suggest the presence of aggregation bias in the literature, implying that the empirical studies based on aggregated data may provide biased results.
Keywords: 330; Interest Rate Pass-Through; Bias; Mazedonien